2018
DOI: 10.3390/ijms19082179
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Ca2+ Increases and Connexin 43 Hemichannel Opening Are Necessary but Not Sufficient for Thy-1-Induced Astrocyte Migration

Abstract: Under pro-inflammatory conditions, astrocytes become reactive and acquire a migratory phenotype. Our results show that hemichannels formed by connexin 43 (Cx43) play an important role in Thy-1-induced astrocyte migration. The neuronal protein Thy-1 binds to αvβ3 integrin in astrocytes, thereby leading to intricate signaling pathways that include calcium (Ca2+) release from intracellular stores, opening of Cx43 hemichannels, release of ATP, activation of P2X7 receptor, and Ca2+ influx. However, because these Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…Higher adhesion frequencies of Syndecan-4 with Thy-1-Fc wild type [Thy-1(RLD)-Fc] compared to the control conditions with TRAIL-R2-Fc receptor (TRAIL-R2-Fc) or beads without proteins (Buffer) were observed ( Figure 1B ). TRAIL-R2-Fc is an Fc-tagged protein that serves as a negative control in all our functional assays ( Maldonado et al, 2017 ; Lagos-Cabré et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Higher adhesion frequencies of Syndecan-4 with Thy-1-Fc wild type [Thy-1(RLD)-Fc] compared to the control conditions with TRAIL-R2-Fc receptor (TRAIL-R2-Fc) or beads without proteins (Buffer) were observed ( Figure 1B ). TRAIL-R2-Fc is an Fc-tagged protein that serves as a negative control in all our functional assays ( Maldonado et al, 2017 ; Lagos-Cabré et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, this finding led to the idea that Cx43 played a relevant role in regulating astrocytic mobility. Since then, several studies have reported that Cxs affect astrocyte migration (Homkajorn et al, 2010;Kotini and Mayor, 2015;Lagos-Cabre, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…5,6 CaSR increases the concentration of intracellular calcium ([Ca 2+ ] i ) by up-regulation of the IP3-PLC pathway. 7 Ca 2+ promotes cell proliferation by activating ERK and PI3K-Akt pathways. 7,8 Our current study showed that CaSR was ex-…”
mentioning
confidence: 99%
“…7 Ca 2+ promotes cell proliferation by activating ERK and PI3K-Akt pathways. 7,8 Our current study showed that CaSR was ex-…”
mentioning
confidence: 99%